The use of 3D ceramic block graft compared with autogenous block graft for rehabilitation of the atrophic maxilla: a randomized controlled clinical trial - de Almeida Malzoni, Carolina Mendonça [UNESP]; Gonçalves, Victor [UNESP]; Possari, Juliana [UNESP]; Junior, Elcio Marcantonio [UNESP] (Springer Nature, 2022)
Background: Dental implant placement may require a bone graft for vertical and horizontal alveolar ridge augmentation. Due to its osteoconduction, osteoinductive, and osteogenesis, autogenous bone graft characteristics are considered the standard gold treatment. However, autografts can promote postoperative morbidity and implicate difficulties concerning the graft adaptation to the recipient's bone since it can eventually avoid gaps. To overcome these issues, this trial will compare the performance of Plenum® Oss 3Dβ fit, an alloplastic graft, and a 3D-printed patient-specific graft based on β-tricalcium phosphate to the autograft procedure. Methods: This is a split-mouth randomized clinical study designed to evaluate the performance of personalized (patient-specific) bioceramic bone grafts (Plenum® Oss 3Dβ fit) for bone augmentation of the atrophic anterior maxilla in comparison to the autogenous bone graft. We hypothesize that the gain and maintenance of the grafted area volume and the quality of the newly formed bone tissue after eight months postoperative with the synthetic patient-specific graft will be superior to the autogenous bone graft. To assess the quantity and the quality of bone neoformation, volumetric and histological analyses will be performed. Discussion: The fabrication of medical devices by additive manufacturing presents advantages over conventional manufacturing processes, mostly related to the precision of geometry and anatomy. Additionally, the osteoconductive proprieties of β-tricalcium phosphate enable this synthetic bone substitute as an alternative solution over autogenous graft for bone defect reconstruction. Thus, patient-specific bone grafts can potentially improve patient satisfaction, reducing the need for autogenous bone grafts, consequently avoiding implications related to this type of treatment, such as patient morbidity. Trial registration: This study is registered in REBEC (Registro Brasileiro de Ensaios Clínicos): RBR-76wmm3q; UTN: U1111-1272-7773. Registration date: 14 September 2021.
Keywords: 3D-printed bone graft; Atrophic maxilla; Patient-specific bone graft; Synthetic bone substitute; β-tricalcium phosphate